Resonant photoproduction of e⁺e⁻-pair with photon emission in strong magnetic field - Fomin, P.I.; Kholodov, R.I. (Вопросы атомной науки и техники, 2007)
The quantum-electrodynamic process of electron-positron pair production by a photon is considered in a strong external magnetic field. The process is accompanied by emission of the final photon. Kinematics and resonance conditions are found in ultraquantum approximation, namely the approximation of the strong magnetic field and low-excited states of an electron and a positron. The resonance conditions are realized, if the energy of the final photon equals to the distance between the Landau levels of an electron. A probability of the resonance electron-positron pair production with photon emission is found in the form of the Breit-Wigner cross section. This value is comparable with the probability of e⁺e⁻-pair production without photon emission.